ANALISIS NILAI TAMBAH PRODUK TURUNAN MADU PADA CV. MADU APIARI MUTIARA CIMANGGIS, DEPOK, JAWA BARAT - Fahmi Noval Amar; Eny Dwiningsih; Armaeni Dwi Humaerah (Departement of Agribusiness Faculty of Science and Technology, 2017)
The purposes of this study are: 1) to determine the ratio of added values, productivities, and distribution margins resulting from any derived products of honey, and 2) to determine the efficiency of derived products of honey during the period of analysis from 2012 until 2013. The research was carried out in the CV. Madu Apiari Mutiara located in Depok, West Java. The hayami method, the productivity ratio and the R/C ratio were employed to analyze the data. Results from data analyses showed that the average value added per production of the whole product is Rp 20,892.90, - or the value added ratio 35.65 % on an average. The product with the highest productivity of all is honey shampoo. Overall, the R/C value on an average amounted to 1.90 that means business efficiency of derived products of honey is profitable and feasible to be developed.